Accuracy of serum neurofilament light to identify contrast-enhancing lesions in multiple sclerosis - Bose, Gauruv; Healy, Brian C; Barro, Christian; Moreira Ferreira, Vanessa F; Saxena, Shrishti; Glanz, Bonnie I; Lokhande, Hrishikesh A; Polgar-Turcsanyi, Mariann; Bakshi, Rohit; Weiner, Howard L; Chitnis, Tanuja (Multiple sclerosis, 2023)
Contrast-enhancing magnetic resonance imaging (MRI) lesions (CELs) indicate acute multiple sclerosis inflammation. Serum biomarkers, neurofilament light (sNfL), and glial fibrillary acidic protein (sGFAP) may increase in the presence of CELs, and indicate a need to perform MRI. We assessed the accuracy of biomarkers to detect CELs. Patients with two gadolinium-enhanced MRIs and serum biomarkers tested within 3 months were included ( = 557, 66% female). Optimal cut-points from Bland-Altman analysis for spot biomarker level and Youden's index for delta-change from remission were evaluated. A total of 116 patients (21%) had CELs. A spot sNfL measurement >23.0 pg/mL corresponded to 7.0 times higher odds of CEL presence (95% CI: 3.8, 12.8), with 25.9% sensitivity, 95.2% specificity, operating characteristic curve (AUC) 0.61; while sNfL delta-change >30.8% from remission corresponded to 5.0 times higher odds (95% CI: 3.2, 7.8), 52.6% sensitivity, 81.9% specificity, AUC 0.67. sGFAP had poor CEL detection. In patients > 50 years, neither cut-point remained significant. sNfL delta-change outperformed spot levels at identifying asymptomatic CELs (AUC 0.67 vs 0.59) and in patients without treatment escalation between samples (AUC 0.67 vs 0.57). Spot sNfL >23.0 pg/mL or a 30.8% increase from remission provides modest prediction of CELs in patients <50 years; however, low sNfL does not obviate the need for MRI.